2023
DOI: 10.3390/genes14101859
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inheritance Models of Non-Syndromic Cleft Lip with or without Palate: From Monogenic to Polygenic

Xi Cheng,
Fengzhou Du,
Xiao Long
et al.

Abstract: Non-syndromic cleft lip with or without palate (NSCL/P) is a prevalent birth defect that affects 1/500–1/1400 live births globally. The genetic basis of NSCL/P is intricate and involves both genetic and environmental factors. In the past few years, various genetic inheritance models have been proposed to elucidate the underlying mechanisms of NSCL/P. These models range from simple monogenic inheritance to more complex polygenic inheritance. Here, we present a comprehensive overview of the genetic inheritance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…NSCLP is associated with various factors, and the pathogenesis of NSCLP is not completely clear. It is believed that susceptibility genes are closely related to NSCLP caused by abnormal palatal morphogenesis and tissue fusion during embryonic development [24,[27][28][29]. A variety of approaches have been used to identify key genes contributing to NSCLP through linkage analysis, genomic rearrangements, candidate genes, and genome-wide association studies (GWAS) [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCLP is associated with various factors, and the pathogenesis of NSCLP is not completely clear. It is believed that susceptibility genes are closely related to NSCLP caused by abnormal palatal morphogenesis and tissue fusion during embryonic development [24,[27][28][29]. A variety of approaches have been used to identify key genes contributing to NSCLP through linkage analysis, genomic rearrangements, candidate genes, and genome-wide association studies (GWAS) [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, these observations suggested that different populations have different causal variants due to different genetic backgrounds., Leslie and Marazita reviewed orofacial clefts with the many error genes that contributed to the etiology of birth defects [23]. Few studies have explored genomic loci mutation related to NSCLP among Chinese people [24].…”
Section: Introductionmentioning
confidence: 99%
“…OFC is a complex congenital anomaly exhibiting an interaction between genetic and environmental factors [57]. Although cleft lip and cleft palate often occur together, NSCL/P and NSCPO are two distinct groups of NSOFC based on embryological and epidemiological distinction [58].…”
Section: Discussionmentioning
confidence: 99%